A New Variety of Abrus Precatorius L. (Fabaceae) From Bangladesh (Bangladesh Journal of Plant Taxonomy, 2021)
A new variety Abrus precatorius L. var. albo-spermum Hassan, Rahman et Afroz, var. nov. is described and illustrated from Bangladesh. The new variety is closest to Abrus preactorius L., but differs by its white coloured oval shaped seeds, short gynoecium which is half the length of longer filaments and with a short style.Bangladesh J. Plant Taxon. 28(2): 289-294, 2021 (December)